Dynamic Proteomic and miRNA Analysis of Polysomes from Isolated Mouse Heart After Langendorff Perfusion - Stastna, Miroslava; Thomas, Amandine; Germano, Juliana; Pourpirali, Somayeh; Van Eyk, Jennifer E; Gottlieb, Roberta A (Journal of visualized experiments, 2018)
Studies in dynamic changes in protein translation require specialized methods. Here we examined changes in newly-synthesized proteins in response to ischemia and reperfusion using the isolated perfused mouse heart coupled with polysome profiling. To further understand the dynamic changes in protein translation, we characterized the mRNAs that were loaded with cytosolic ribosomes (polyribosomes or polysomes) and also recovered mitochondrial polysomes and compared mRNA and protein distribution in the high-efficiency fractions (numerous ribosomes attached to mRNA), low-efficiency (fewer ribosomes attached) which also included mitochondrial polysomes, and the non-translating fractions. miRNAs can also associate with mRNAs that are being translated, thereby reducing the efficiency of translation, we examined the distribution of miRNAs across the fractions. The distribution of mRNAs, miRNAs, and proteins was examined under basal perfused conditions, at the end of 30 min of global no-flow ischemia, and after 30 min of reperfusion. Here we present the methods used to accomplish this analysis-in particular, the approach to optimization of protein extraction from the sucrose gradient, as this has not been described before-and provide some representative results.
Keywords: Animals; Heart; RNA, Messenger; srdce; MicroRNAs; Proteomics; polyribozomy; zvířata; Polyribosomes; proteomika; Mice; messenger RNA; mikro RNA; myši